An Analysis of Customer Satisfaction Determinants at PDAM Tirtanadi, Medan Sunggal Branch - Assya Maya Siregar; Abdul Azis Syarif; Uun Novalia Harahap (Indonesian Journal of Aviation Science and Engineering, 2025)
This study aims to identify the supporting and inhibiting factors influencing the quality of drinking water services at PDAM Tirtanadi Sunggal Branch, using Zeithaml and Bitner’s framework with indicators of reliability, responsiveness, assurance, empathy, and tangibility as the measurement standards. A qualitative approach was applied, utilizing questionnaires, observations, and documentation to gather data. The findings reveal that the water service operations are adequate but not yet optimal. Several quality indicators expected to serve as benchmarks were not fully implemented, resulting in services that remain less productive. Supporting factors include the availability of adequate infrastructure and the commitment of employees to serve customers, while inhibiting factors involve limited resources, inconsistent service delivery, and insufficient responsiveness to customer complaints. Overall, the study concludes that while PDAM Tirtanadi Sunggal Branch demonstrates potential to improve its performance, systematic efforts are required to optimize all quality indicators to achieve a higher standard of service.